Relationship between CYP3A5 Polymorphism and Tacrolimus Blood Concentration Changes in Allogeneic Hematopoietic Stem Cell Transplant Recipients during Continuous Infusion - Naoki Yoshikawa; Hidemi Takeshima; Masaaki Sekine; Keiichi Akizuki; Tomonori Hidaka; Kazuya Shimoda; Ryuji Ikeda (MDPI AG, 2021)
A polymorphism in the gene encoding the metabolic enzyme cytochrome P450 family 3 subfamily A member 5 (CYP3A5) is a particularly influential factor in the use of tacrolimus in Japanese patients. Those who are homozygotic for the *3 mutation lack CYP3A5 activity, which results in substantial individual differences in tacrolimus metabolism. The aim of this study was to analyze the relationship between individual differences in tacrolimus blood concentration changes and CYP3A5 polymorphisms in allogeneic hematopoietic stem cell transplantation recipients during the period of increasing blood concentration of the drug following treatment onset. This was a prospective observational cohort study, involving 20 patients administered tacrolimus by continuous infusion. The subjects were divided into the *1/*3 and *3/*3 groups based on CYP3A5 polymorphism analysis. The tacrolimus blood concentration/dose (C/D) ratio increased from day 1 and was largely stable on day 5, and a significant difference was observed between the *1/*3 and *3/*3 groups in the time course of the C/D ratio during this period (p < 0.05). This study reveals the effects of CYP3A5 polymorphism on continuous changes in tacrolimus blood concentration.